MEDIA PEMBELAJARAN INTERAKTIF BERDIFERENSIASI UNTUK MENINGKATKAN KOMPETENSI GURU - Hartini, Hartini; Herawati, Ratna; Wahyuningsih, Hartati Dyah; Haryanto, Haryanto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Differentiated interactive learning media are innovative teaching aids that can be tailored to the individual needs of each student. By integrating technology and different teaching strategies, this media allows teachers to deliver subject matter in a way that is more interesting, effective, and in accordance with the learning styles and abilities of each student. This Community Service activity was organized in collaboration with SMK N 1 Musuk Boyolali and the Faculty of Computer Science, Dharma AUB University Surakarta. The results of community service where training is carried out, teachers prefer to create interactive learning materials using WordWall tools. Because there are many themes and choices, the form of making interesting material for students. Wordwall is a web-based platform that can be used to create learning media, the use of differentiated interactive learning media, teacher competence can be improved, so they can provide a more meaningful learning experience for students.